The Struggle of Fiqh Reasoning in the Implementation of MUI’s Fatwa on Worship during Pandemic in the Island of Lombok - Muhammad War'i (Jurnal Dialog, 2021)
This paper discusses the implementation of MUI’s fatwa on worship during Covid-19 pandemic. Social facts show that the implementation of the fatwa has given rise to various socio-religious conflicts in Lombok island. Through a qualitative approach, the paper concludes: First, the people of Lombok Muslim community disapprove the fatwa. Second, there is a conceptual difference between the government as the beholder of the MUI’s fatwa and the community's religious traditions that have been maintained for a long time. Third, the model of fiqh law reasoning used by the government in general is a textual (normative) model that is contrary to society's use of historical meaning. Therefore, a dialogical process is needed for a solution to social problems that occur as a result of the implementation of the ulama’s fatwa which is used as government policy so that it does not appear to be coercive by involving elements of ulama, goverment, and society. The dialog conectivity of these three elements in negotiating their understandings of fiqh to place the intent and purpose of a legal product (fatwa) will encourage the realization of inclusive fiqh reasoning. Keywords: fiqh reason, MUI’s fatwa, mosque closing Tulisan ini mengkaji secara fenomenologis implementasi fatwa MUI tentang ibadah di tengah pandemi wabah Covid-19. Fakta sosial menunjukkan bahwa implementasi fatwa tersebut telah melahirkan berbagai konflik sosial keagamaan di Pulau Lombok. Melalui pendekatan kualitatif tulisan berkesimpulan: Pertama, Respon masyarakat muslim Lombok sebagai demografi dengan banyaknya masjid adalah adanya ketidakmenerimaan baik secara psikologis, sosial, dan kultural. Kedua, Terjadi pertentangan konseptual antara pemerintah selaku pemegang fatwa MUI dengan konsep tradisi keagamaan masyarakat yang telah lama ada dan menjadi pedoman mereka. Ketiga, model penalaran hukum fikih yang digunakan pemerintah secara umum adalah model pemaknaan tekstual (normatif) bertentangan dengan masyarakat yang menggunakan pemaknaan historis. Oleh karena itu, dibutuhkan proses dialogis sebagai langkah solutif atas problem sosial yang terjadi akibat implementasi fatwa ulama yang dijadikan kebijakan pemerintah agar tidak terkesan memaksa dengan melibatkan unsur ulama, umara’, dan mujtama’. Konektivitas dialog tiga unsur ini dalam menegosiasikan pemahaman fikih mereka untuk mendudukkan maksud dan tujuan suatu produk hukum (fatwa) akan mendorong terwujudnya nalar fikih yang inklusif. Kata Kunci: nalar fikih, fatwa MUI, penutupan masjid